2000
DOI: 10.1016/s0002-9440(10)64836-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Fas-Ligand Expression in Mouse Keratinocytes during UV Carcinogenesis

Abstract: The incidence of skin cancer far exceeds the incidences of all other human cancers combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
89
0
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 34 publications
(42 reference statements)
11
89
0
3
Order By: Relevance
“…TUNEL assay data indicated the absence of TUNEL-positive cells in mouse skin irradiated with UV light for 8 weeks. This was expected because we showed previously that chronic UV irradiation results in apoptosis resistance (Ouhtit et al, 2000a). However, TUNEL-positive cells were also absent in the epidermis of mice at all time points after UV irradiation discontinuation (data not shown), suggesting that decreased epidermal hyperplasia was not due to apoptosis.…”
Section: Timesupporting
confidence: 75%
See 2 more Smart Citations
“…TUNEL assay data indicated the absence of TUNEL-positive cells in mouse skin irradiated with UV light for 8 weeks. This was expected because we showed previously that chronic UV irradiation results in apoptosis resistance (Ouhtit et al, 2000a). However, TUNEL-positive cells were also absent in the epidermis of mice at all time points after UV irradiation discontinuation (data not shown), suggesting that decreased epidermal hyperplasia was not due to apoptosis.…”
Section: Timesupporting
confidence: 75%
“…We have previously shown that exposure of SKH-hr1 mice to chronic UV radiation induced SCCs (Ouhtit et al, 2000a). UV-signature CC-TT and C-T mutations in p53 codons 154-155, 175-176, and 270 or 275 were detected in epidermis as early as after 1 week of chronic UV irradiation (Ouhtit et al, 2000a).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These findings provided strong evidence that UVB triggers the CD95 apoptotic pathway by directly activating the CD95 receptor. In another study, Ouhtit et al 18 reported early (3 hours after acute UV exposure) up-regulation of Fas in the skin of hairless mice accompanied by increase in its ligand. However, prolonged overexpression of Fas and the loss of expression of the ligand were observed with chronic (weeks) UV irradiation.…”
Section: Discussionmentioning
confidence: 93%
“…Chronic exposure to sunlight (as evidenced by the presence of solar elastosis), up-regulates Fas expression, which extends up to the granular layer, similar to the experimental data. 12,18,19 With further sun-induced skin damage resulting in AK, which represents the earliest morphologic stage in development of skin carcinoma, there was marked down-regulation, or total loss of CD95 expression. This down-regulation was retained in invasive SCC.…”
Section: Discussionmentioning
confidence: 99%